(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic hepatitis is a prolonged inflammatory liver disease, primarily caused by viral infections (HBV, HCV), autoimmune reactions, or toxic exposures. The chronic inflammatory process may result in hepatocyte injury, fibrosis, and cirrhosis, which determine the severity of the disease and the risk of complications.